Specific in vitro initiation of transcription on the adenovirus type 2 early and late EII transcription units. - Mathis, D J (1981)
Three transcription units are present in the adenovirus type 2 region EII. Transcription units EIIaE and EIIaL encode the mRNA for the 72,000-dalton DNA binding protein, early and late in the lytic cycle, respectively, and transcription unit EIIb encodes the mRNA for the protein that binds to the 5' termini of adenovirus DNA. By using a cell-free transcription system in the presence of purified RNA polymerase B (or II), we have obtained specific initiation of transcription from both the EIIaE promoter, which does not contain a T-A-T-A box, and the EIIaL promoter, which does. In addition, we have identified a new EII T-A-T-A box promoter that is located close to the early non-T-A-T-A box promoter and is used both in vivo and in vitro.